MATHEMATICAL CRITICAL THINKING SKILL OF MADRASAH IBTIDAIYAH STUDENTS ON CUBES AND BEAM VOLUMES MATERIAL - Anas Salahudin; Inne Marthyane Pratiwi; Syaeful Hidayat (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
This research-based on the findings that elementary school students already have mathematical critical thinking skills but have not reached the whole stage of the skills. Critical thinking skills of mathematics is essential for students because critical mathematical thinking can solve the problems and as a consideration to make decisions. This research aims to: (1) explore the critical thinking skills of mathematics of the subject of the volume of cubes and beams; (2) to determine student's difficulties in solving mathematical critical thinking skills test questions on the subject of the volume of cubes and beams. The research used a case study method of 28 students in one of the Islamic elementary schools in Bandung Regency. The data collected in the form of qualitative data obtained through tests of mathematical critical thinking skills, interviews, and document analysis. Data analysis techniques used thematic analysis by analyzing students' learning trajectory. The results showed that most students were still in the low category in the ability of critical thinking. As for the difficulties experienced by students, namely in providing simple explanations and working on problems that are not systematic. For this reason, the improving of students' mathematical critical thinking skills need further research.